Community care for the Elderly: Needs and Service Use Study (CENSUS): Who receives home care packages and what are the outcomes?. (21st April 2014) - Low, Lee‐Fay; Fletcher, Jennifer; Gresham, Meredith; Brodaty, Henry
<x xml:space="preserve">Abstract</x> Aim Investigate factors associated with waiting times for home care packages and outcomes for care recipients and carers. Method Analyses of data collected every four months for 12 months from 55 community‐dwelling older adults eligible for government‐subsidised packaged care and their carers. Results Thirty of fifty‐five participants were offered a package; they waited from one to 237 days. Baseline quality of life was higher for those offered a package than those not. Baseline care needs and unmet needs, neuropsychiatric symptoms, and cognitive decline did not predict offers. Package receipt compared to non‐package receipt was associated with decreased carer burden over time but did not affect levels of unmet care needs, care needs or quality of life. Conclusions Being offered a home care package was not based on waiting time or unmet care needs. Reforms should include a transparent system of wait listing and prioritisation.